Закони визначення процесів в середині науки в дослідженні розвитку теорії управління вищими навчальними закладами в Україні - Васиньова, Надія; Vasineva, N.S. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто наукові наробки, у яких схарактеризовано групу законів та закономірностей розвитку педагогічної науки, що є основою аналізу розвитку теорії управління вищими навчальними закладами в Україні. На основі аналізу зроблено висновки, що, по-перше, закони та закономірності розвитку педагогічної науки дозволяють наблизитися до проникнення в сутність її парадигми, зрозуміти процеси, які відбуваються в науці, визначити перспективи подальшого розвитку та засоби впливу на цей розвиток. По-друге, урахування законів та закономірностей, що визначають процеси в середині науки в дослідженні розвитку теорії управління вищими навчальними закладами, дозволяють: виокремити внутрішні та зовнішні чинники, що і зумовлюють розвиток теорії управління вищими навчальними закладами; з’ясувати характер потреб практики, що були поштовхом для проведення наукових досліджень у той чи інший період часу та оцінки впливу їх результатів на цю практику; з’ясувати співвідношення управлінської науки та управлінської практики. The article deals with scientific developments, which describe a group of laws and the regularities of pedagogical science development: the laws and regularities that determine the methodological foundations of pedagogy; laws and regularities that define the processes within a science; laws and regularities that characterize the connections of pedagogy with external factors. Awareness of the laws and regularities of the pedagogical science development allows getting closer to penetrate into the essence of its paradigms, to understand the processes that occur in the science, to determine the prospects for further development and ways of influencing this development. In the study of the problem of development of higher education institutions’ management theory the laws and the regularities of pedagogical science development constitute the methodological bases of research. The author substantiates the laws and the regularities that determine the processes within a science as the basis for the analysis of higher education institutions’ management theory. The following conclusions based on the analysis are made, firstly, the laws and the regularities of pedagogical science development allows getting closer to penetrate into the essence of its paradigms, to understand the processes that occur in the science, to determine the prospects for further development and ways of influencing this development. Secondly, the accounting of laws and regularities that determine the processes within a science in the study of higher education institutions’ management theory, allows to: separate internal and external factors that stipulate the development of higher education institutions’ management theory; determine the nature of management practices requirements, which were the impetus for research in a given period of time and evaluate their results’ impact on the practice; analyze how education institutions’ management theory was correlated with management practices in the monitoring period; to find out whether the management theory advanced the management practice.
The laws of process determination within a science in the study of development of higher education institutions’ management theory in Ukraine
Keywords: закони; laws; закономірності; розвиток; педагогічна наука; теорія управління; управлінська наука; вищі навчальні заклади; regularities; development; pedagogical science; management theory; management science; higher education institutions